Keluwesan Berdakwah dalam Pelestarian Tradisi Pesisir: Kajian Mengenai Bilasan pada Kegiatan Sedekah Laut di Kabupaten Rembang - Badruzzaman Badruzzaman (Jurnal Bimas Islam, 2015)
Abstract Jokowi government maritime discourse, presupposes a fisherman as the spearhead of development, to be the fresh air for the welfare of fishermen archipelago. The welfare of fishermen symbolized by the coastal tradition, based on fishermen rationality, it reflects the bounding needs of fishermen communities, safety and fish catches. Bring up the interrelationships shaped symbolic ceremony, which is understood differently among groups of fishermen. It came to be the various charity events with variety rituals and entertainment. The results of self-actualization of a fishermen group called Babagan. Sometimes for this purpose, Babagan become very generous, even beyond the financial capabilities of their own. They are the creation of local wisdom into the Sea Charity (Sedekah Laut). The Elders are flexible in responding on the variety creations. It comes to be the element of da’wah, Bilasan. This awareness creates open interaction between Babagan in the fishing village of Rembang district views. Bilasan in a series of Sea Charity (Sedekah Laut) studied as a representation Babagan Pupils in cultural dynamics typical of fishermen, as well as one aspect of Islam Nusantara local wealth. Abstraksi Wacana di bidang kemaritiman pada pemerintahan Jokowi, mengandaikan nelayan sebagai ujung tombak pembangunan, menjadi angin segar bagi kesejahteraan nelayan Nusantara. Kesejahteraan nelayan disimbolkan dengan tradisi pesisir, berdasarkan rasionalitas nelayan, merefleksikan keterikatan kebutuhan masyarakat nelayan, keselamatan dan hasil tangkapan ikan. Memunculkan hubungan timbal balik berbentuk upacara simbolik, yang dipahami berlainan antar kelompok nelayan. Muncullah kegiatan sedekah laut dengan ragam ritual dan hiburan. Hasil aktualisasi diri kelompok nelayan yang disebut Babagan. Terkadang demi tujuan ini, Babagan bersikap sangat royal, bahkan melebihi kemampuan finansial mereka sendiri. Mereka mengkreasikan kearifan lokal ke dalam Sedekah Laut. Para Sesepuh bersikap luwes saat menanggapi ragam kreasi tersebut. Masuklah unsur dakwah, Bilasan. Kesadaran tersebut mewarnai interaksi terbuka antar Babagan yang ada di kampung nelayan Pandangan kabupaten Rembang. Bilasan dalam rangkaian Sedekah Laut dikaji sebagai representasi Babagan Santri dalam dinamika budaya khas nelayan, sekaligus sebagai salah satu aspek kekayaan lokal Islam Nusantara.